A Consensus Statement on the Terminology for Automated Visual Field Abnormalities. Issue 4 (18th December 2022) - Kruger, Joshua M.; Almer, Zina; Almog, Yehoshua; Aloni, Eyal; Bachar-Zipori, Anat; Bialer, Omer; Ben-Bassat Mizrachi, Iris; Horowitz, Josepha; Huna-Baron, Ruth; Ivanir, Yair; Jabaly-Habib, Haneen; Klein, Ainat; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: A multitude of terms have been used to describe automated visual field abnormalities. To date, there is no universally accepted system of definitions or guidelines. Variability among clinicians creates the risk of miscommunication and the compromise of patient care. The purposes of this study were to 1) assess the degree of consistency among a group of neuro-ophthalmologists in the description of visual field abnormalities and 2) to create a consensus statement with standardized terminology and definitions. Methods: In phase one of the study, all neuro-ophthalmologists in Israel were asked to complete a survey in which they described the abnormalities in 10 selected automated visual field tests. In phase 2 of the study, the authors created a national consensus statement on the terminology and definitions for visual field abnormalities using a modified Delphi method. In phase 3, the neuro-ophthalmologists were asked to repeat the initial survey of the 10 visual fields using the consensus statement to formulate their answers. Results: Twenty-six neuro-ophthalmologists participated in the initial survey. On average, there were 7.5 unique descriptions for each of the visual fields (SD 3.17), a description of only the location in 24.6% (SD 0.19), and an undecided response in 6.15% (SD 4.13). Twenty-two neuro-ophthalmologists participated in the creation of a consensus statement which included 24 types of abnormalities with specific definitions. Twenty-three neuro-ophthalmologists repeated the survey using the consensus statement. On average, in the repeated survey, there were 5.9 unique descriptions for each of the visual fields (SD 1.79), a description of only the location in 0.004% (SD 0.01), and an undecided response in 3.07% (SD 2.11%). Relative to the first survey, there was a significant improvement in the use of specific and decisive terminology. Conclusions: The study confirmed a great degree of variability in the use of terminology to describe automated visual field abnormalities. The creation of a consensus statement was associated with improved use of specific terminology. Future efforts may be warranted to further standardize terminology and definitions.